Company Performance Moderates the Relationship between Carbon Emission Disclosure and Eco-Efficiency on Company Value - Lesmana, Indra; Nofryanti, Nofryanti; Tatariyanto, Firman (PINISI Discretion Review, 2025)
This study examines the moderating role of company performance in the relationship between carbon emission disclosure, eco-efficiency, and firm value, with Return on Assets (ROA) as the moderating variable. The research focuses on non-financial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2023 period. Using a causal associative quantitative approach, panel data regression analysis was conducted with EViews version 13 to test direct and interaction effects. The findings reveal that eco-efficiency has a statistically significant partial effect on enhancing firm value. In contrast, carbon emission disclosure exhibits no significant impact on firm value. Furthermore, company performance (ROA) fails to moderate or strengthen the relationship between carbon emission disclosure, eco-efficiency, and firm value. These results suggest that eco-efficiency practices play a critical role in driving corporate valuation, whereas carbon emission disclosures remain undervalued by market stakeholders. The study highlights the need for firms to prioritize operational eco-efficiency over voluntary environmental disclosures to align sustainability efforts with financial outcomes. This research provides empirical insights for corporate managers, investors, and policymakers to refine strategies that integrate environmental accountability with value creation in emerging markets.